2012
DOI: 10.1186/1471-2342-12-22
|View full text |Cite
|
Sign up to set email alerts
|

Is single reading with computer-aided detection (CAD) as good as double reading in mammography screening? A systematic review

Abstract: BackgroundIn accordance with European guidelines, mammography screening comprises independent readings by two breast radiologists (double reading). CAD (computer-aided detection) has been suggested to complement or replace one of the two readers (single reading + CAD).The aim of this systematic review is to address the following question: Is the reading of mammographic x-ray images by a single breast radiologist together with CAD at least as accurate as double reading?MethodsThe electronic literature search in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 69 publications
0
56
0
2
Order By: Relevance
“…However, its contribution to routine screening remains a question of debate. In a systematic review, Azavedo et al concluded that there is insufficient evidence to determine whether CAD could replace a second reader [31]. On the other hand, recent studies have shown that the addition of breast tomosynthesis to digital mammography improves the cancer detection rate in mammography screening and may reduce false positive referrals [32,33].…”
Section: Discussionmentioning
confidence: 98%
“…However, its contribution to routine screening remains a question of debate. In a systematic review, Azavedo et al concluded that there is insufficient evidence to determine whether CAD could replace a second reader [31]. On the other hand, recent studies have shown that the addition of breast tomosynthesis to digital mammography improves the cancer detection rate in mammography screening and may reduce false positive referrals [32,33].…”
Section: Discussionmentioning
confidence: 98%
“…Environmental factors such as changes in reproductive patterns, physical inactivity, and obesity also play a major role in BC incidence [8,9]. With an aim of improving patient prognosis and survival in BC, newer techniques have been introduced, including full-field digital mammography (FFDM), digital breast tomosynthesis, and computer-aided tomography [10,11]. The management of BC also depends on various factors, such as tumor stage, menopausal status, histological features, and patient age [12].…”
Section: Introductionmentioning
confidence: 99%
“…4 When comparing dual to single reading, studies have shown that sensitivity increased by 5-10% without a significant effect on recall rates. 5 Consensus arbitration of discordant double read cases also improved reading performance since it decreased recall rates and increased Positive Predictive Value (PPV). 4,6,7 Since consensus arbitration was not practised locally, as per radiologists' choice, women who were recalled by one radiologist experienced additional examinations during further assessment clinics.…”
Section: Introductionmentioning
confidence: 99%